O trabalho docente na rede pública do estado de São Paulo: apontamentos iniciais para a discussão da jornada de trabalho - Fernandes, Maria José da Silva [UNESP]; Barbosa, Andreza (My University, 2014)
The changes in the world of work that, in turn, directly affect the teaching work, have expanded the processes of precariousness and intensification, contributing for deteriorating conditions which teachers use to labor. Considering that the time designated for teaching activities is an important part of work conditions, we look for, in this article, to analyze the work shift of teachers in São Paulo state educational public system. Regarding that teachers are a very heterogeneous group, we have chosen to discuss the workday those professionals who dedicate themselves in the last years of elementary and high school. Through a literature review and a research about the legislation related to the topic, in Brazil and São Paulo state, we have highlighted that the teachers’ work shifts should include not only the time for classroom activities, but also for other extra activities. Moreover, we emphasize that the state of São Paulo government has promoted, since 2012, a reformulation of the teachers’ work shift that has not properly include the appropriate length of time for extra educational activities, contrasting the parameters founded in the national legislation. Besides the legal non-compliance, that fact has accentuated the process of intensification of teaching work, contributing for the embrittlement of the collective activities.

Los cambios en el sitio de trabajo que, a su vez, afectan directamente el trabajo de la enseñanza, amplian los procesos de precarización y la intensificación, lo que contribuye a la degradación de las condiciones reales en las que trabajan los maestros. Teniendo en cuenta que el tiempo asignado a las actividades de enseñanza es una parte importante de las condiciones de trabajo, en este artículo tratamos de analizar la jornada de los maestros de las escuelas públicas del estado de São Paulo. Dado que los profesores forman un grupo muy heterogéneo, se optó por discutir la jornada de los que se dedican al último año de la escuela primaria y de la escuela media. A través de una revisión de la literatura sobre el tema, y estudio acerca de la legislación relacionada con la temática en Brasil, y en el estado de São Paulo, subrayamos que las horas de trabajo de los profesores deben incluir no sólo el tiempo necesario para las actividades en la sala de clase, así como actividades adicionales. También señalamos que el estado de São Paulo promovió, en 2012, una reforma de la jornada laboral de sus profesores, que no incluye adecuadamente el tiempo necesario para realizar las actividades extracurriculares, yendo en contra lo que establece la legislación nacional. Además del incumplimiento legal, este hecho pone de relieve la intensificación del trabajo de los profesores, lo que contribuye al debilitamiento de las actividades colectivas.

As mudanças no mundo do trabalho que, por sua vez, afetam diretamente o trabalho docente, ampliam os processos de precarização e intensificação contribuindo para a degradação das condições efetivas nas quais os professores atuam. Considerando que o tempo destinado às atividades docentes é parte importante das condições de trabalho, buscamos neste artigo analisar a jornada dos professores da rede pública estadual paulista. Tendo em vista que os docentes formam um grupo bastante heterogêneo, optamos por discutir a jornada de trabalho daqueles que se dedicam aos anos finais do Ensino Fundamental e Ensino Médio. Por meio de uma revisão de literatura sobre o assunto e do levantamento da legislação relacionada à temática, no Brasil e no estado de São Paulo, destacamos que as jornadas de trabalho dos professores devem contemplar não apenas o tempo necessário para as atividades desenvolvidas em sala de aula, como também as atividades extraclasse. Destacamos ainda que o estado de São Paulo promoveu, a partir de 2012, uma reformulação da jornada de trabalho de seus professores que não contempla adequadamente o tempo necessário para a realização das atividades extraclasse, contrariando o que a legislação nacional estabelece. Além do não cumprimento legal, tal fato acentua o processo de intensificação do trabalho docente contribuindo para a fragilização das atividades coletivas.
Teaching work at São Paulo state public system: initial notes for the discussion of the work day
El trabajo docente en la educación pública del estado de São Paulo: puntos de partida para discutirse la jornada laboral
Keywords: The State of São Paulo; Teachers’ work shift; Teaching work; Estado de São Paulo; Jornada laboral docente; Trabajo docente; Estado de São Paulo; Jornada de trabalho docente; Trabalho docente